Exploring cyberfeminism and technology as recrafting tools of the girl child’s image and identity in Where the Lion Stalks and When You Dance with the Crocodile, and Americanah - Shikongo, Luise Ndapanda (Namibia University of Science and Technology, 2022)
This research is an exploration of cyberfeminism and technology as recrafting tools of the girl child’s image and identity in Where the Lion Stalks and When You Dance with the Crocodile, and Americanah. Hence, the study applied the Literary theory of cyberfeminism to the selected texts. This study posited that using technology can empower the girl child to narrate her individual experiences and the collective experiences (discrimination, oppression, abuse, and trauma) of other women. Using the selected texts, the study showed that the girl child deconstructs stereotypical ideas that still exist in various parts of Africa portraying technology as a complex phenomenon for women and cyberspace as a dangerous platform for women especially the girl child. The main objective of this study was to explore cyberfeminism and technology as recrafting tools of the girl child’s image and identity in selected female authored texts. The sub-objectives were: Firstly, to interrogate how the girl child utilises technology to conscientise society on issues affecting women in the selected female authored texts. Secondly, to explore how cyberspace recrafts the girl child’s image in the selected female authored texts. Thirdly, to examine how technology empowers the girl child and reconstructs her identity in the selected female authored texts. This research employed a qualitative research design and found that, in the three selected texts (Americanah, When you Dance with the Crocodile and When Lion Stalks), the girl-child protagonists (Ifemelu and Helena) have no position to voice the issues encountered in a patriarchal and Marxist society because it is prohibited. To this end, it is revealed that through the use cyberspace as a platform to vocalise issues that affect women in the present and in the past, as well as in Africa and in the diaspora. Moreover, the study discovered that Adichie’s Americanah (2013) and Muller’s (2012) When you Dance with Crocodile and Where the Lion Stalks (2016) depicts the girl-child redefining and liberating her image using cybersace and technology. As Ifemelu use her blog she is able to affirm her stance and cultures thus creating her own image as opposed to allowing herself to get diverted into a foreign culture. Thus, with re-emphasis, she gains support from the online community. Lastly, the findings revealed that Adichie focused attention on the facet of cyberfeminism which deals with the cybernetic identity formation as a novel way of mediating a sense of self. The cyberspace created by technology in Adichie’s novel facilitated an alternative space for the girl child to find self-expression. Identity formation seemed quite crucial as it encompassed several traits, one of which centred on the hair.
Supervisor: Dr Juliet Pasi Co- Supervisor: Dr Vida De Voss
Keywords: Namibia; Cyberfeminism; Cyberspace; Technology; Girl-child; Identity; Image; Americanah; When you Dance with the Crocodile; Where the Lion Stalks